2006
DOI: 10.1093/sleep/29.12.1573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atomoxetine and Methylphenidate on Sleep in Children With ADHD

Abstract: Patients receiving twice-daily atomoxetine had shorter sleep-onset latencies, relative to thrice-daily methylphenidate, based on objective actigraphy and polysomnography data. Although both medications decreased nighttime awakenings, the decrease was greater for methylphenidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
4
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 0 publications
10
108
4
7
Order By: Relevance
“…Some studies suggest that methylphenidate, a common pharmacotherapy for ADHD, may exacerbate these sleep problems (Corkum et al, 2008;Galland et al, 2010;Ironside et al, 2010;Sangal et al, 2006;Schwartz et al, 2004). We show here that in healthy adult mice, methylphenidate alone can alter both sleep and circadian rhythmicity.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Some studies suggest that methylphenidate, a common pharmacotherapy for ADHD, may exacerbate these sleep problems (Corkum et al, 2008;Galland et al, 2010;Ironside et al, 2010;Sangal et al, 2006;Schwartz et al, 2004). We show here that in healthy adult mice, methylphenidate alone can alter both sleep and circadian rhythmicity.…”
Section: Discussionsupporting
confidence: 49%
“…The change in phase angle is also consistent with findings from placebocontrolled and baseline-comparison human studies examining the effects of methylphenidate on various sleep and circadian markers. Longer sleep latency and decreased total sleep time were observed in people given methylphenidate (Boonstra et al, 2007;Corkum et al, 2008;Galland et al, 2010;Sangal et al, 2006;Schwartz et al, 2004). A phase delay in circadian locomotor rhythms has also been noted (Ironside et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…If the SLEEP, ATTENTION, AND EXECUTIVE FUNCTIONING number of counts exceeds the threshold, the epoch is scored as wake; if the number is equal or below the threshold, the epoch is scored as sleep. Threshold was set at medium (40 activity counts), which has been used in previous studies experimenting with the same device and similar population (e.g., Sangal et al, 2006). An event marker button was used to indicate bedtime and rising time.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12][13] Some of the randomized controlled comparison studies for efficacy and safety of these two agents found MPH was superior while some others did not find any difference between two agents. 9,10,12,14,15 The metaanalyses of those studies also show similar contradictions. [16][17][18][19] Therefore, there is still a need for the studies comparing MPH and ATX which are two agents frequently used in the treatment of ADHD.…”
mentioning
confidence: 73%